2012
DOI: 10.1158/1078-0432.ccr-12-1380
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Genetic, and Epigenetic Aspects of Base and Nucleotide Excision Repair in Colorectal Carcinomas

Abstract: Purpose: DNA repair capacity (DRC) is a determinant not only of cancer development but also of individual response to therapy. Previously, altered base and nucleotide excision repair (BER and NER) have been described in lymphocytes of patients with sporadic colorectal cancer. We, for the first time, evaluate both excision repair capacities in human colon biopsies to study their participation in colorectal tumorigenesis.Experimental design: Seventy pairs of tumor and adjacent healthy tissues were analyzed for B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 46 publications
3
62
2
Order By: Relevance
“…Additional information about DNA damage that could be associated with CA, and about individual ability to deal with this damage, could be obtained by determining DNA damage markers, such as DNA adducts or DNA double-strand breaks, and DNA repair capacity (54). Such studies may help in understanding the genotoxic burden present in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additional information about DNA damage that could be associated with CA, and about individual ability to deal with this damage, could be obtained by determining DNA damage markers, such as DNA adducts or DNA double-strand breaks, and DNA repair capacity (54). Such studies may help in understanding the genotoxic burden present in the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the in vitro DNA repair assay as a suited biomarker in human biomonitoring studies considering influences of occupation, environmental, or lifestyle factors as well as of repair gene polymorphisms (Collins and Azqueta 2012), and the test application not only in cell culture and animal studies, but also in human, occupational, and nutritional studies , were recently reviewed. In addition, the assay was adjusted to measure BER-and NER-specific DNA repair capacity in tissues of different transformation stages using seventy pairs of tumor and adjacent healthy colon tissue samples (Slyskova et al 2012). The analysis revealed that colon tumor cells are not deficient in BER and NER, but rather show individual characteristics.…”
Section: Dna Repairmentioning
confidence: 99%
“…22,24 Slyskova et al demonstrated that the expression of four nucleotide excision repair genes (CSB, CCNH, XPA, and XPD) and four base excision repair genes (NEIL1, APEX1, OGG1, and PARP1) was 1.08-to 1.28-fold higher in colorectal carcinomas (P < 0.05). 25 In addition, it is known that deficient nucleotide excision repair greatly increases the risk of melanoma and other skin cancers because of defective repair of UV radiation-induced lesions in skin cells after sun exposure. 2 Cancer is an evolutionary disease fueled by genomic instability that is often caused by chromosomal translocations, which can lead to aberrant expression of oncogenes, such as c-Myc or Jab1/ CSN5, or to the generation of deregulated chimeric proteins with enhanced activity.…”
Section: Ercc1mentioning
confidence: 99%